Management accounting education a challenge in facing the 21st century - Mas'ud Machfoedz (Jurnal Akuntansi dan Auditing Indonesia)
Since the beginnig of 1980s, business have been challenged by some problems, such as the keener competition and world-wide competition. The major cause of those problems is the changing business paradigm from producer-driven to customer-driven. Advanced technology that has replaced the traditional and manual technology has accelerated the companies to change their business style. Accordingly, accounting education should respond to the change of business paradigm by improving its curriculum to be in line with the new paradigm. For the same reason, the Accounting Education Curriculum Committee (AECC) in the USA has changed its curriculum by including three major components in their courses : skill, character, and knowledge. Unfortunately, in Indonesia, changes in the curriculum as a response to this new paradigm is relatively slow compared to those in developed countries. This is due to die concentration of its accounting education which would rather produce management accountants than public accountants. Data from study show that the increase in the number of management accountants is faster than that of public accountants. This condition should be anticipated by betterment of management accounting education.